SUSTAINABLE WASTE ALTERNATIVE AS CEMENT REPLACEMENT IN PAVEMENT STABILIZATION - Michiel HEYNS; Mohamed MOSTAFA HASSAN; Samuel Olugbenga ABEJIDE ABEJIDE (Journal of Construction Project Management and Innovation)
In recent years, the philosophy of recycling has taken a grip of national development all round the world. This results in a growing demand to minimise waste and foster recycling of products such as Fly-Ash. Several million tonnes of Fly-Ash is being produced every day globally and the disposal of the Fly-Ash represents a serious obstacle to the electricity industries in South Africa. Accumulations of these fly-Ash landfill dump sites have reached alarming high levels, requiring immediate attention for its disposal. Solutions to reduce landfill sites from waste by-products of coal combustion are becoming critical due to the increased growth in landfill sites yearly. This study proposes a reduction in Fly-Ash landfill waste and its suitability for use in pavement construction as a cement replacement in stabilizing subgrade, sub-base and base course layers in South African roads. The method adopted constitutes testing Fly-Ash for use as a substitute engineering material for soil stabilisation in pavement construction.